Analisis Kesesuaian Lahan Wilayah Pesisir Kota Bengkulu melalui Perancangan Model Spasial dan Sistem Informasi Geografis (SIG) - Yulian Fauzi; Boko Susilo; Zulfia Memi Mayasari (Forum Geografi, 2009)
This research is aimed to alocate land management and use coastal and ocean area Sub-Province base on digital through Geographical Information System (GIS). This research was done in the coastal area Kota Bengkulu, through spatial alocate analysis and land suitability analysis for brackish water fish ponds, maritime tourism and conservation areas. Approach used in this research is spatial analysis to parameter/variable and land suitability criteria consist of element abiotik, biotik, culture, and spatial use (RTRW). Land suitability analysis is done by using SIG through overlay technique. Result of research indicate that from 7 sub district of coastal area of exist in Kota Bengkulu, land suitability (S1) for brackish water fish ponds are found in sub-district Muara Bangkahulu and Kampung Melayu. Land suitability (S1) for the maritime tourism are found in sub-district Teluk Segara and Ratu Samban, while Land suitability (S1) for conservation area of are found in sub-district Kampung Melayu.